The first data on the innervation of the lophophore in the rhynchonelliform brachiopod Hemithiris psittacea: what is the ground pattern of the lophophore in lophophorates? - Elena N. Temereva; Tatyana V. Kuzmina (BMC Evolutionary Biology, 2017)
Abstract Background The nervous system in brachiopods has seldom been studied with modern methods. An understanding of lophophore innervation in adult brachiopods is useful for comparing the innervation of the same lophophore type among different brachiopods and can also help answer questions about the monophyly of the lophophorates. Although some brachiopods are studied with modern methods, rhynchonelliform brachiopods still require investigation. The current study used transmission electron microscopy, immunocytochemistry, and confocal laser scanning microscopy to investigate the nerve system of the lophophore and tentacles in the rhynchonelliform Hemithiris psittacea. Results Four longitudinal nerves pass along each brachium of the lophophore: the main, accessory, second accessory, and lower. The main brachial nerve extends at the base of the dorsal side of the brachial fold and gives rise to the cross nerves, passing through the extracellular matrix to the tentacles. Cross nerves skirt the accessory brachial nerve, branch, and penetrate into adjacent outer and inner tentacles, where they are referred to as the frontal tentacular nerves. The second accessory nerve passes along the base of the inner tentacles. This nerve consists of Ʊ-like parts, which repetitively skirt the frontal and lateral sides of the inner tentacle and the frontal sides of the outer tentacles. The second accessory nerve gives rise to the latero-frontal nerves of the inner and outer tentacles. The abfrontal nerves of the inner tentacles also originate from the second accessory nerve, whereas the abfrontal nerves of the outer tentacles originate from the lower brachial nerve. The lower brachial nerve extends along the outer side of the lophophore brachia and gives rise to the intertentacular nerves, which form a T-like branch and penetrate the adjacent outer tentacles where they are referred to as abfrontal nerves. The paired outer radial nerves start from the lower brachial nerve, extend into the second accessory nerve, and give rise to the lateroabfrontal tentacular nerves of the outer tentacles. Conclusions The innervation of the lophophore in the rhynchonelliform Hemithiris psittacea differs from that in the inarticulate Lingula anatina in several ways. The accessory brachial nerve does not participate in the innervation of the tentacles in H. psittacea as it does in L. anatina. The second accessory nerve is present in H. psittacea but not in L. anatina. There are six tentacular nerves in the outer tentacles of H. psittacea but only four in all other brachiopods studied to date. The reduced contribution of the accessory brachial nerve to tentacle innervation may reflect the general pattern of reduction of the inner lophophoral nerve in both phoronids and brachiopods. Bryozoan lophophores, in contrast, have a weakened outer nerve and a strengthened inner nerve. Our results suggest that the ancestral lophophore of all lophophorates had a simple shape but many nerve elements.